Proceedings of the 8th International Conference on Attosecond Science and Technology - Argenti, Luca; Chini, Michael; Fang, Li (Springer Proceedings in Physics,, 2024)
This open access volume brings together selected papers from the 8th International Conference on Attosecond Science and Technology. The contributions within represent the latest advances in attosecond science, covering recent progress in ultrafast electron dynamics in atoms, molecules, clusters, surfaces, solids, nanostructures and plasmas, as well as the generation of sub-femtosecond XUV and X-ray pulses, either through table-top laser setups or with X-ray free-electron lasers. In addition to highlighting key advances and outlining the state of the field, the conference and its proceedings serve to introduce junior researchers to the community, promote collaborations, and represent the global and topical diversity of the field.